Characterization of cardiac involvement in children with LMNA-related muscular dystrophy - Cesar, Sergi; Campuzano, Oscar; Cruzalegui, Jose; Fiol, Victori; Moll, Isaac; Martínez-Barrios, Estefania; Zschaeck, Irene; Natera-de Benito, Daniel; Ortez, Carlos; Carrera, Laura; Expósito, Jessica; Berrueco, Rubén; et al. (Frontiers in Cell and Developmental Biology, 2023)
LMNA-related muscular dystrophy is a rare entity that produce “laminopathies” such as Emery–Dreifuss muscular dystrophy (EDMD), limb–girdle muscular dystrophy type 1B (LGMD1B), and LMNA-related congenital muscular dystrophy (L-CMD). Heart failure, malignant arrhythmias, and sudden death may occur. No consensus exists on cardiovascular management in pediatric laminopathies. The aim was to perform an exhaustive cardiologic follow-up in pediatric patients diagnosed with LMNA-related muscular dystrophy. Baseline cardiac work-up consisted of clinical assessment, transthoracic Doppler echocardiography, 12-lead electrocardiogram, electrophysiological study, and implantation of a long-term implantable cardiac loop recorder (ILR). We enrolled twenty-eight pediatric patients diagnosed with EDMD (13 patients), L-CMD (11 patients), LGMD1B (2 patients), and LMNA-related mild weakness (2 patients). Follow-up showed dilated cardiomyopathy (DCM) in six patients and malignant arrhythmias in five (four concomitant with DCM) detected by the ILR that required implantable cardioverter defibrillator (ICD) implantation. Malignant arrhythmias were detected in 20% of our cohort and early-onset EDMD showed worse cardiac prognosis. Patients diagnosed with early-onset EDMD are at higher risk of DCM, while potentially life-threatening arrhythmias without DCM appear earlier in L-CMD patients. Early onset neurologic symptoms could be related with worse cardiac prognosis. Specific clinical guidelines for children are needed to prevent sudden death.